Preparation and Optical Limiting Properties of Multiwalled Carbon Nanotubes with ð-Conjugated Metal-Free Phthalocyanine Moieties - BLAU, WERNER (My University, 2009)
Phthalocyanines (Pcs) usually exhibit stronger optical limiting response that can be used to protect human eyes, optical elements, and sensors from intense laser pulses. New unsymmetrically substituted metal-free phthalocyanine-covalently functionalized multiwalled carbon nanotubes (PcH(2)-MWNTs), in which the wt % of MWNTs in the resulting product was found to be 35%, were synthesized. A considerably quenching of the fluorescence intensity was found in the photoluminescence spectrum of PcH(2)-MWNTs. This observation suggests a quenching of the singlet excited PcH(2) by the covalently linked MWNTs. This material exhibits strong scattering at higher intensities, which evidently comes from the MWNT counterpart. The nonlinear response of tBu(3)NH(2)PcH(2) is due to reverse saturable absorption (RSA), while that of PcH(2)-MWNTs is due to both RSA and nonlinear scattering, which could be two conflicted mechanisms for optical limiting, giving rise to suppression of the whole nonlinear response of PcH(2)-MWNTs.
PUBLISHED
Keywords: Optics; Phthalocyanines (Pcs); Nanoscience & Materials